Management of arterial complications in abdominal surgery - علي, سليمان (Latakia University Journal -Medical Sciences Series, 2022)
Arterial damage can occur in a defferent proportion according to the surgical procedure on the abdomen , and this is related to the specialization ( digestive , urinary , and gynecological ) , The surgeon's experience and the conditions of the surgical work . Iatrogenic mecahanisms about 10% of the mechanisms of the traumatic abdominal arteries . in this research, we have studied the arterial complications following surgical operations on the abdomen , their frequency , degree of danger , and the most important preventive methods to avoid their occurrence. This research confirms the need for the surgeon to know the emergency management and to be able to determine the type of injury caused and the degree of its severity and the request of the vascular surgeon to carry out the management flour to stop the bleeding and vascular repair without causing the injury to become more severe .